Student loans as the answer to lack of resources for higher education - Tilak, Jandhyala B.G. (1999)
Student loan programmes, as the answer to the problem of lack of public funds for higher education, are based on a questionable philosophy and unrealistic assumptions and are being launched in many developing countries with exaggerated expectations. - Reproduced
Keywords: Students; Education; Higher education